A multicenter cohort study of thyroidectomy-related decision regret in patients with low-risk papillary thyroid microcarcinoma - Genpeng Li; Ruicen Li; Jinjing Zhong; Wenjie Chen; Jinhao Shuai; Meizhu Chen; Feng Deng; Tao Wei; Huairong Tang; Zhihui Li; Jianyong Lei (Nature Communications)
Abstract The level of thyroidectomy-related regret in patients with clinically low-risk papillary thyroid microcarcinoma (PTMC) and the determinants of decision regret are largely unknown. Here, we show that 319 (24.2%) of those who undergo thyroidectomy and 4 (3.4%) who undergo active surveillance (AS) express heightened regret based on validated decision regret scale (DRS) scores in the first online survey (P < 0.001). Multivariable analysis and the second online survey for patients with heightened regret confirm that postoperative lower thyroid cancer-specific quality of life (QoL) (scar and psychology) (75.5%) is the most common factor for heightened regret of thyroidectomy, followed by preoperative understanding of disease [not at all] (15.0%), presentation of complications (3.8%) and other factors (5.7%). These results highlight that more caution should be exercised when low-risk PTMC patients are scheduled for thyroidectomy. Information about the various treatments for clinically low-risk PTMC, the risk of thyroidectomy and postoperative QoL should be fully communicated during initial counseling.